Method for advanced treatment of wastewater based on surface catalytic ozonation

CN120081485BActive Publication Date: 2026-10-27SICHUAN UNIV +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510297176.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-03-13
Publication Date
2026-10-27
Estimated Expiration
2045-03-13

AI Technical Summary

Technical Problem

[0006]针对现有臭氧催化氧化水处理过程由游离自由基物种主导,氧化过程易受到水体共存基质的干扰,导致氧化剂有效利用率和氧化效率降低的问题,本发明提供了一种基于表面催化臭氧氧化的废水深度处理方法,通过构建表面吸附态活性氧物种介导的臭氧氧化过程来提高废水处理方法对水体基质的抗干扰能力并提高污染物降解效率,以更好地满足实际复杂废水体系中有机污染物降解的需求

Benefits of technology

[0029]1.本发明提供了一种基于表面催化臭氧氧化的废水深度处理方法,该方法以含有CuO和Co3O4异质结构的纳米级铜钴双金属催化剂为基础,成功构建了表面吸附态活性氧物种介导的臭氧氧化过程,采用本发明所述方法进行废水处理的过程中,催化剂催化臭氧产生吸附于催化剂表面的表面羟基自由基和表面原子氧降解废水中的有机污染物。由于本发明所述方法在废水处理过程中催化剂催化臭氧产生的降解有机污染物的活性氧物种是吸附于催化剂表面的,相对于游离的活性氧物种,表面吸附态活性氧物种能够保持更高的氧化能力和更长的存活寿命,可解决现有臭氧催化氧化水处理过程以游离自由基物种主导而存在的氧化过程易受到水体共存基质影响的问题,有利于提高氧化剂的有效利用率及氧化效率并降低废水处理成本,能更好地满足实际复杂废水体系中有机污染物降解的需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120081485B_ABST
    Figure CN120081485B_ABST
Patent Text Reader

Abstract

The present application belongs to the field of wastewater treatment, and provides a wastewater advanced treatment method based on surface catalytic ozone oxidation, which comprises the following steps: continuously or batchwise adding wastewater from the upper part of a closed wastewater treatment device into the closed wastewater treatment device, adding a catalyst into the wastewater, continuously introducing a gas containing ozone into the wastewater from the lower part of the closed wastewater treatment device for wastewater treatment, collecting ozone tail gas generated in the wastewater treatment process at the top of the closed wastewater treatment device and discharging the ozone tail gas after harmless treatment, and continuously or batchwise discharging the treated wastewater; in the wastewater treatment process, the catalyst catalyzes ozone to generate surface hydroxyl radicals and surface atomic oxygen adsorbed on the surface of the catalyst to degrade organic pollutants in the wastewater; and the catalyst is a nanoscale copper-cobalt bimetallic catalyst. The present application can improve the anti-interference ability of the wastewater treatment method to water body matrix and improve the pollutant degradation efficiency, and can better meet the needs of actual complex wastewater treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of wastewater treatment and relates to a method for deep wastewater treatment based on surface catalytic ozone oxidation. Background Technology

[0002] The compliant discharge and reuse of industrial wastewater are crucial for ensuring water quality safety and ecological health, and for promoting the resource utilization of wastewater. Industrial wastewater contains recalcitrant organic pollutants, such as pharmaceuticals and personal care products, endocrine disruptors, and synthetic chemicals. These pollutants are characterized by complex composition, stable structure, and long half-lives, making them difficult to remove effectively using traditional physicochemical and biochemical treatment technologies. This is one of the key challenges currently facing the achievement of compliant discharge and reuse of industrial wastewater. In recent years, advanced oxidation-based deep treatment technologies have become an important means of treating recalcitrant and toxic organic pollutants due to their high efficiency and low cost, and are widely used in practical wastewater treatment.

[0003] Advanced oxidation technology (AOC) is a typical environmental remediation technology for removing recalcitrant organic pollutants. It primarily uses transition metals as catalysts to activate hydrogen peroxide (H₂O₂), persulfate (PMS / PDS), and permanganate (MnO₂). 4- Oxidants such as ozone (O3) and peracetic acid (PAA) generate highly oxidizing free radicals that transform organic pollutants into harmless or less harmful chemical substances. Among these, ozone catalytic oxidation technology has become one of the most widely used advanced wastewater treatment technologies in practical engineering due to its advantages such as high oxidation efficiency, on-site ozone generation eliminating transportation risks, and almost no sludge production.

[0004] Traditional heterogeneous catalytic ozone oxidation technology mainly relies on catalysts to catalyze ozone to generate free hydroxyl radicals, thereby achieving efficient removal of pollutants. Free hydroxyl radicals have high redox potentials, but their oxidation reactions are non-selective. In addition to reacting with target pollutants, they also readily react with coexisting organic matter and inorganic anions (such as humic acid and chloride ions) in water bodies, thus significantly affecting the effective utilization of the oxidant, reducing oxidation efficiency, and increasing operating costs.

[0005] In recent years, researchers both domestically and internationally have discovered that, in addition to free radical species, surface-adsorbed reactive oxygen species, such as surface hydroxyl radicals and surface atomic oxygen, also exist in some heterogeneous advanced oxidation systems. Compared to bulk free radical species, surface-adsorbed reactive oxygen species can maintain higher oxidation capacity and longer lifespan. Their mediated oxidation reactions mostly occur on the catalyst surface, thus exhibiting strong resistance to interference from the coexisting matrix in water bodies. However, currently, most reactive oxygen species generated during the catalytic ozone oxidation reaction of heterogeneous catalysts are free radical species, and the ozone oxidation process remains dominated by free radical species. The lack of methods for constructing ozone oxidation processes mediated by surface-adsorbed reactive oxygen species limits the development of ozone catalytic oxidation technology mediated by surface-adsorbed reactive oxygen species and its application and promotion in the efficient removal of recalcitrant organic pollutants. Therefore, constructing ozone oxidation processes mediated by surface-adsorbed reactive oxygen species and using this as a basis for advanced wastewater treatment will be of great significance for improving the resistance to interference in wastewater treatment methods and increasing the treatment efficiency of water pollution. Summary of the Invention

[0006] To address the problem that existing ozone catalytic oxidation water treatment processes are dominated by free radical species and are easily affected by the coexisting matrix in the water, leading to reduced effective utilization and oxidation efficiency of the oxidant, this invention provides a wastewater deep treatment method based on surface catalytic ozone oxidation. By constructing an ozone oxidation process mediated by surface-adsorbed active oxygen species, the method improves the resistance of wastewater treatment to water matrix interference and enhances pollutant degradation efficiency, thereby better meeting the needs of organic pollutant degradation in complex wastewater systems.

[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0008] The wastewater deep treatment method based on surface catalytic ozone oxidation includes the following steps:

[0009] Wastewater is continuously or batch-added into a closed wastewater treatment device from the top. A catalyst is added to the wastewater, and ozone-containing gas is continuously introduced into the wastewater from the bottom for treatment. The ozone tail gas generated during the wastewater treatment process is collected at the top of the closed wastewater treatment device and discharged after harmless treatment. The treated wastewater is discharged continuously or in batches. During the wastewater treatment process, the catalyst catalyzes ozone to generate surface hydroxyl radicals and surface atomic oxygen adsorbed on the catalyst surface, which degrade organic pollutants in the wastewater. The catalyst is a nano-scale copper-cobalt bimetallic catalyst, which is composed of CuO and Co3O4, and CuO and Co3O4 form a heterostructure.

[0010] In the above-mentioned advanced wastewater treatment method, the catalyst is prepared as follows: copper source and ZIF-67 are added to a solvent at a mass percentage of (40%–60%):(40%–60%), reacted fully at 120–240°C, separated into solid and liquid phases, the obtained solid phase is washed with solvent, and then pulverized to obtain a reaction precursor. The reaction precursor is calcined at 350–550°C for 1–5 hours, washed to remove unreacted substances from the calcined product, dried, and pulverized to obtain the catalyst.

[0011] In the above-mentioned advanced wastewater treatment method, when preparing the catalyst, it is preferable to control the reaction time between the copper source and ZIF-67 at 120–240°C for 4–12 hours. The solvent used in catalyst preparation is at least one of water, methanol, ethanol, and N,N-dimethylformamide. The heating method used in catalyst preparation can be oil bath heating, hydrothermal reaction vessel heating, microwave heating, etc.

[0012] In the above-mentioned advanced wastewater treatment method, when preparing the catalyst, the copper source is a water-soluble divalent copper salt, and the water-soluble divalent copper includes at least one of copper nitrate, copper chloride, copper acetate, and copper sulfate.

[0013] In the above-mentioned advanced wastewater treatment method, the reaction precursor is calcined in an atmosphere of air, oxygen, or a mixture of air and oxygen when preparing the catalyst.

[0014] In the aforementioned advanced wastewater treatment method, during catalyst preparation, the precursor is calcined at 350–550°C for 1–5 hours. The washing process to remove unreacted substances from the calcined product includes one or more of the following methods: water washing, alcohol washing, and acid washing. For alcohol washing, the alcohol solvent used includes at least one of methanol and ethanol. For acid washing, the acid solvent used includes at least one of dilute hydrochloric acid, dilute sulfuric acid, and dilute nitric acid.

[0015] In the above-mentioned advanced wastewater treatment method, the preparation method of ZIF-67 is as follows: A cobalt source and dimethylimidazole are thoroughly mixed in a solvent at a mass percentage of (37%–47%):(53%–63%), reacted at 20–50°C for 0.5–4 hours, and then allowed to settle at room temperature for 24–48 hours to obtain the final product. The cobalt source is a water-soluble divalent cobalt salt, which includes at least one of cobalt nitrate, cobalt chloride, cobalt sulfate, and cobalt acetate. The solvent used in the preparation of ZIF-67 is at least one of water, methanol, ethanol, and N,N-dimethylformamide.

[0016] In the aforementioned advanced wastewater treatment method, the catalyst is nanoscale in size, typically meaning less than 1 micrometer. During wastewater treatment, the nanoscale catalyst can achieve sufficient dispersion and contact with pollutants in the wastewater under the influence of water flow and ozone-containing gas flow, eliminating the need for stirring or other dispersion methods to promote sufficient contact between the catalyst and pollutants.

[0017] In the aforementioned advanced wastewater treatment method, the catalyst is a copper-cobalt bimetallic catalyst constructed using ZIF-67 as a template, utilizing the unique dodecahedral morphology of ZIF-67 to uniformly disperse copper and cobalt while retaining the original morphology of ZIF-67. ZIF-67 possesses characteristics such as large specific surface area, uniform pore size, and uniform pore distribution, which enhances the adsorption of copper ions and promotes a more uniform distribution of cobalt and copper sites in the copper-cobalt bimetallic catalyst after calcination. This, in turn, increases the number of Lewis acidic sites on the catalyst surface, strengthening the adsorption and decomposition of ozone by the cobalt and copper sites. Simultaneously, the catalyst forms a heterostructure with CuO and Co3O4, and the electron transfer between CuO and Co3O4 improves the catalyst's redox performance and electron transfer performance, thereby enhancing the catalyst's ozone activation performance.

[0018] In the aforementioned advanced wastewater treatment method, the dosage of catalyst in the wastewater is related to the wastewater quality (e.g., the type and concentration of pollutants). In practical applications, once the wastewater quality is determined, the catalyst dosage can be determined experimentally. Typically, the catalyst dosage in the wastewater can be controlled between 0.2 and 10 g / L.

[0019] In the aforementioned advanced wastewater treatment method, the amount of ozone-containing gas continuously introduced into the wastewater of the closed-loop wastewater treatment device is related to the wastewater quality (e.g., the types and concentrations of pollutants). In practical applications, once the wastewater quality is determined, the ozone dosage can be determined experimentally. Typically, ozone-containing gas can be introduced into the wastewater of the closed-loop wastewater treatment device at a rate of 0.4–5 mmol of ozone per minute per liter of wastewater. The ozone-containing gas is either ozone-containing air or ozone-containing oxygen.

[0020] The present invention has demonstrated through experiments that when wastewater with a pH value of 3 to 11 is treated using the method of the present invention, the organic pollutants in the wastewater all have a high mineralization rate. Therefore, in the above-mentioned advanced wastewater treatment method, the pH value of the wastewater can usually be controlled to be 3 to 11.

[0021] In the aforementioned advanced wastewater treatment methods, the wastewater treatment time is determined based on actual application needs. For example, it can be determined based on factors such as the removal rate of the target pollutant and the degree of change in a certain water quality indicator. The specific wastewater treatment time is related to factors such as the wastewater quality, the amount of catalyst added, and the amount of ozone added. Generally, when using a continuous wastewater inflow and continuous wastewater outflow method, the hydraulic retention time of the wastewater in the closed-loop wastewater treatment process is controlled to be 30–120 minutes; when using a batch wastewater inflow and batch wastewater outflow method, the wastewater treatment time is controlled to be 20–180 minutes.

[0022] In the above-mentioned advanced wastewater treatment method, the wastewater temperature is usually controlled at room temperature (e.g., 5-40℃, 10-35℃) during the wastewater treatment process, and there is generally no need to perform special temperature control on the wastewater.

[0023] In the above-mentioned advanced wastewater treatment method, the closed-loop wastewater treatment device can be a commonly used device for wastewater treatment using ozone catalytic oxidation technology, such as a bubbling reaction tower, a fluidized bed reactor, or a tubular reactor.

[0024] In the above-mentioned advanced wastewater treatment method, the method for harmlessly treating the ozone exhaust gas generated during the wastewater treatment process can refer to existing ozone exhaust gas treatment methods and use existing ozone exhaust gas treatment devices for harmless treatment.

[0025] In the above-mentioned advanced wastewater treatment method, the types of pollutants contained in the wastewater include pharmaceutical pollutants, industrial chemicals, organic nitrogen pollutants, etc., and the wastewater can be secondary effluent from industrial wastewater, such as secondary effluent from chemical wastewater, secondary effluent from pharmaceutical wastewater, etc.

[0026] This invention demonstrates through experiments that, after five cycles, the catalyst in the above-mentioned advanced wastewater treatment method exhibits a mineralization rate of only 5% lower than when the catalyst was first used when catalyzing ozone oxidation to degrade sulfamethoxazole. This is still 30% higher than the mineralization rate of sulfamethoxazole using a simple ozone system. This indicates that the catalyst used in this invention has excellent recyclability when catalyzing ozone oxidation to degrade organic pollutants. In actual wastewater treatment, it can be recycled multiple times to reduce wastewater treatment costs. The number of times the catalyst can be recycled is determined according to actual application requirements; for example, the catalyst can be recycled 5 to 10 times.

[0027] This invention experimentally demonstrates that when wastewater contains inorganic anions such as chloride and sulfate ions that readily react with free hydroxyl radicals, the degradation capacity of the method described in this invention for pollutants in the wastewater is not affected by the coexisting inorganic anions. For example, when the concentration of coexisting chloride ions in the wastewater is more than 600 times that of the target pollutant sulfamethoxazole, the mineralization capacity of the method described in this invention for sulfamethoxazole is not adversely affected. Therefore, the method described in this invention can be used to treat wastewater containing inorganic anions, organic acids, and other matrices, and can meet the requirements for the degradation of organic pollutants in complex aquatic matrices.

[0028] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0029] 1. This invention provides a method for advanced wastewater treatment based on surface-catalyzed ozone oxidation. This method utilizes a nanoscale copper-cobalt bimetallic catalyst containing CuO and Co3O4 heterostructures to successfully construct an ozone oxidation process mediated by surface-adsorbed active oxygen species. During wastewater treatment using this method, the catalyst catalyzes ozone to generate surface hydroxyl radicals and surface atomic oxygen adsorbed on the catalyst surface, which degrade organic pollutants in the wastewater. Because the active oxygen species generated by the catalyst during ozone oxidation for degrading organic pollutants are adsorbed on the catalyst surface, surface-adsorbed active oxygen species maintain higher oxidation capacity and longer lifespan compared to free active oxygen species. This solves the problem that existing ozone catalytic oxidation water treatment processes, dominated by free radical species, are easily affected by the coexisting matrix in the water body. This method is beneficial for improving the effective utilization rate and oxidation efficiency of the oxidant, reducing wastewater treatment costs, and better meeting the needs of organic pollutant degradation in complex wastewater systems.

[0030] 2. Experiments have demonstrated that the method described in this invention has superior effects in degrading and deeply mineralizing recalcitrant pollutants in wastewater. For example, the method described in this invention, with the addition of a catalyst and continuous ozone introduction for 20 minutes, can achieve complete degradation of 0.5 mmol / L oxalic acid, while simply introducing ozone for 30 minutes only achieves a removal rate of 6% for the same concentration of oxalic acid. As another example, the method described in this invention, with the addition of a catalyst and continuous ozone introduction for 60 minutes, achieves a mineralization rate of 60% for 20 mg / L sulfamethoxazole, which is significantly higher than the mineralization rate of sulfamethoxazole with only ozone introduction for 60 minutes.

[0031] 3. Experiments have demonstrated that the ozone oxidation process mediated by surface-adsorbed reactive oxygen species constructed by the method of this invention utilizes surface-adsorbed reactive oxygen species, including surface hydroxyl radicals and surface atomic oxygen, to degrade organic pollutants, significantly improving the method's resistance to interference from aquatic substrates. Under conditions of 50 mmol / L chloride ions (more than 600 times the pollutant concentration), the mineralization performance of sulfamethoxazole by the method of this invention is not adversely affected, meeting the treatment needs of organic pollutants in complex aquatic substrates and effectively improving the treatment efficiency of aquatic environmental pollution.

[0032] 4. Experiments have demonstrated that the catalyst described in this invention exhibits excellent recyclability. In the catalytic ozone degradation of sulfamethoxazole, after five cycles of catalyst recycling, the mineralization rate of sulfamethoxazole decreased by only 5% compared to the initial use, which is still 30% higher than the mineralization rate of sulfamethoxazole in a simple ozone system. Furthermore, the method described in this invention demonstrates good mineralization ability for wastewater with pH values ​​ranging from 3 to 11. These two characteristics are highly advantageous for the practical engineering application of the method described in this invention, not only reducing wastewater treatment costs but also demonstrating superior treatment capabilities for wastewater with a wide pH range.

[0033] 5. Experiments have demonstrated that the method described in this invention achieves a COD removal rate of 70% after 120 minutes of reaction for treating secondary effluent from chemical wastewater. This represents an improvement of approximately 55% compared to the case of continuous ozone introduction alone. Furthermore, the method described in this invention achieves a COD removal rate of 90% after 120 minutes of reaction for treating secondary effluent from pharmaceutical wastewater. This represents an improvement of approximately 35% compared to the case of continuous ozone introduction alone. This indicates that the method described in this invention also possesses excellent treatment capabilities for actual wastewater and has potential application value in practical wastewater treatment. Attached Figure Description

[0034] Figure 1 This is the X-ray diffraction pattern of the catalyst prepared in Example 1.

[0035] Figure 2 These are transmission electron microscope (TEM) and high-resolution TEM images of the catalyst prepared in Example 1.

[0036] Figure 3 This is the result of the oxalic acid removal rate test in Example 1.

[0037] Figure 4 This is the result of the quenching experiment in Example 1.

[0038] Figure 5 This is the test result of the sulfamethoxazole mineralization rate in Example 2.

[0039] Figure 6 This is Example 2, which shows the effect of coexisting chloride ions on the mineralization rate of sulfamethoxazole.

[0040] Figure 7 This is the test result of the sulfamethoxazole mineralization rate during the catalyst recycling process in Example 2.

[0041] Figure 8 This is the test result of the sulfamethoxazole mineralization rate in simulated wastewater with different pH values ​​in Example 2.

[0042] Figure 9 This shows the change in chemical oxygen demand (COD) of the secondary effluent from chemical wastewater in Example 10 over treatment time.

[0043] Figure 10 This shows the change in chemical oxygen demand (COD) of the secondary effluent from pharmaceutical wastewater in Example 11 over time. Detailed Implementation

[0044] The following examples further illustrate the advanced wastewater treatment method based on surface catalytic ozone oxidation described in this invention. It should be noted that the following examples are only for further illustration of this invention and should not be construed as limiting the scope of protection of this invention. Any non-essential improvements and adjustments made to this invention by those skilled in the art based on the above description are still within the scope of protection of this invention.

[0045] Example 1

[0046] In this embodiment, the copper-cobalt bimetallic catalyst is prepared by the following steps:

[0047] (1) Cobalt nitrate hexahydrate and 2-methylimidazole were added to anhydrous methanol, and the mass percentage of cobalt nitrate hexahydrate to 2-methylimidazole was controlled to be 47%:53% (that is, cobalt nitrate hexahydrate and 2-methylimidazole accounted for 47% and 53% of the total mass of the two, respectively). The mixture was stirred thoroughly and then stirred vigorously at room temperature for 0.5 h. After that, it was allowed to stand at room temperature for 24 h to obtain ZIF-67.

[0048] (2) Add copper nitrate trihydrate and ZIF-67 to anhydrous ethanol, and control the mass percentage of copper nitrate trihydrate and ZIF-67 to be 50%:50% (that is, copper nitrate trihydrate and ZIF-67 account for 50% and 50% of the total mass of the two, respectively). Then transfer it to a stainless steel autoclave with Teflon lining, react at 120°C for 4 hours, filter, wash the obtained solid phase with ethanol, dry, grind, and obtain the reaction precursor.

[0049] (3) The reaction precursor was placed in a muffle furnace and calcined at 350°C for 2 hours in an air atmosphere. The calcined product was washed with water to remove unreacted substances and then ground to obtain a copper-cobalt bimetallic catalyst with a particle size in the nanometer range.

[0050] Figure 1 This is the X-ray diffraction (XRD) pattern of the catalyst prepared in this embodiment. It can be seen from the figure that the catalyst is composed of CuO and Co3O4. Figure 2 Figures (A) and (B) are transmission electron microscope (TEM) and high-resolution TEM images of the catalyst prepared in this embodiment, respectively. From the figures, it can be determined that CuO and Co3O4 form a heterostructure in the catalyst.

[0051] The following section examines the ability of the catalyst prepared in this embodiment to catalyze the degradation of pollutants by ozone oxidation, and investigates the active species generated during the degradation of pollutants through quenching experiments.

[0052] (1) Investigate the effect of adding a catalyst on the degradation of pollutants.

[0053] Oxalic acid (OA) was used as a model pollutant for advanced wastewater treatment. OA was dissolved in water to form an OA solution with a concentration of 0.5 mmol / L, and this OA solution was used as simulated wastewater.

[0054] Simulated wastewater was added in batches from the top of the bubble column reactor. A catalyst was added to the simulated wastewater at a dosage of 0.4 g / L. After catalyst addition, adsorption treatment was performed for 10 minutes. Then, ozone-containing oxygen was continuously introduced into the simulated wastewater from the bottom of the bubble column reactor at a rate of 0.83 mmol ozone per minute per liter of wastewater. Ozone tail gas generated during wastewater treatment was collected at the top of the bubble column reactor, treated to render it harmless, and then discharged. The treated wastewater was discharged from the bubble column reactor in batches. Samples were taken at 0, 2, 5, 10, 20, and 30 minutes after the ozone-containing oxygen was introduced and filtered through a 0.22 μm filter membrane to test the OA concentration and calculate the OA removal rate. The results are as follows: Figure 3 As shown. By Figure 3 It can be seen that the catalyst has OA adsorption activity, and removes 18% of OA within 10 minutes. When oxygen containing ozone is introduced and reacted for 20 minutes, 100% degradation of OA can be achieved.

[0055] A separate control group for the ozone reaction system was also set up. The operation of the control group was basically the same as the operation described above, except that no catalyst was added. The results were as follows: Figure 3 As shown. By Figure 3 It can be seen that after the adsorption is complete and the reaction continues for 30 minutes, the ozone reaction system alone can only remove 6% of OA.

[0056] (2) Quenching Experiment

[0057] tert-butanol, methanol, and dimethyl sulfoxide (DMSO) were used as quenchers for free hydroxyl radicals, surface-adsorbed hydroxyl radicals, surface hydroxyl radicals, and surface atomic oxygen, respectively.

[0058] OA was dissolved in water to form an OA solution with a concentration of 0.5 mmol / L, which was used as simulated wastewater. Three experimental groups and one blank control group (without quencher) were set up. In the three experimental groups, tert-butanol, methanol, and DMSO were added to the simulated wastewater to a concentration of 200 mmol / L, respectively. Details are as follows:

[0059] Simulated wastewater was added in batches from the top of the bubble column reactor. Appropriate quenching agents (no quenching agent was added to the blank control group) and catalysts were added to each simulated wastewater. After catalyst addition, adsorption treatment was performed for 10 minutes. Then, ozone-containing oxygen was continuously introduced into the simulated wastewater from the bottom of the bubble column reactor at a rate of 0.83 mmol ozone per liter of wastewater per minute. Ozone tail gas generated during wastewater treatment was collected at the top of the bubble column reactor, treated to render it harmless, and then discharged. The treated wastewater was discharged from the bubble column reactor in batches. The catalyst dosage was controlled at 0.4 g / L. Samples were taken and filtered through a 0.22 μm filter membrane at 0, 2, 5, 10, 20, and 30 minutes after the ozone-containing oxygen was introduced, and the OA concentration was tested. The OA removal rate was calculated. The results are as follows: Figure 4 As shown.

[0060] Depend on Figure 4 It can be seen that the OA removal rate was lowest in the experimental group with dimethyl sulfoxide as a quencher, and the degradation of OA was also inhibited to some extent in the experimental group with methanol as a quencher. Since dimethyl sulfoxide is a quencher for surface atomic oxygen and surface hydroxyl radicals, and methanol is a quencher for surface hydroxyl radicals and free hydroxyl radicals, and the OA removal rate in the experimental group with tert-butanol as a quencher was the same as that in the blank control group, this indicates that the main active species generated by the catalyst during the catalytic ozone oxidation degradation of OA do not contain free hydroxyl radicals, but are mainly surface atomic oxygen and surface hydroxyl radicals. That is, the catalyst prepared based on this embodiment can successfully construct the surface catalytic ozone oxidation process.

[0061] Example 2

[0062] In this embodiment, the catalyst prepared in Example 1 is used to catalyze the ozone oxidation degradation of wastewater containing organic pollutants. The steps are as follows:

[0063] (1) Degradation experiment of sulfamethoxazole (SMX)

[0064] SMX was dissolved in water to form an SMX solution with a concentration of 20 mg / L and a pH value between 6 and 7. This SMX solution was used as simulated wastewater.

[0065] Simulated wastewater was added in batches from the top of the bubble column reactor. A catalyst was added to the simulated wastewater at a dosage of 0.4 g / L. Then, ozone-containing oxygen was continuously introduced into the simulated wastewater from the bottom of the bubble column reactor at a rate of 0.83 mmol ozone per liter of wastewater per minute. The ozone exhaust gas generated during the wastewater treatment process was collected at the top of the bubble column reactor, treated to render it harmless, and then discharged. The treated wastewater was discharged from the bubble column reactor in batches. Samples were taken at 0, 15, 30, and 60 minutes after the ozone-containing oxygen was introduced and filtered through a 0.22 μm filter membrane. The total organic carbon (TOC) concentration of the simulated wastewater was tested, and the SMX mineralization rate was calculated. The results are as follows: Figure 5 As shown.

[0066] A separate control group for the ozone reaction system was also set up. The operation of the control group was basically the same as the operation described above, except that no catalyst was added. The results were as follows: Figure 5 As shown.

[0067] Depend on Figure 5 It can be seen that the mineralization rate of SMX in the control group's ozone oxidation system was only 23% after 60 min of reaction, while the mineralization rate of SMX in the method of the present invention reached 60% after 60 min of reaction. This shows that the surface catalytic ozone oxidation process constructed by the method of the present invention under the conditions of adding catalyst and introducing ozone can effectively improve the mineralization ability of pollutants.

[0068] (2) Anti-interference performance test

[0069] Chloride ions (Cl) - (I) are inorganic anions that are commonly found in actual wastewater substrates, and their concentration is often 1 to 2 orders of magnitude higher than that of the target pollutant.

[0070] Two experimental groups and one blank control group were set up. The wastewater sample of the first experimental group was prepared by adding 5 mmol / L chloride ions (5 mM Cl) to SMX solution. - The wastewater sample from the second experimental group was prepared by adding 50 mmol / L chloride ions (50 mM Cl) to an SMX solution. - The wastewater sample for the blank control group was an SMX solution, and the anti-interference performance of the method described in this invention was evaluated.

[0071] Wastewater samples from the two experimental groups and the blank control group were added in batches from the top of the bubble column reactor. A catalyst was added to the wastewater samples at a dosage of 0.4 g / L. Then, ozone-containing oxygen was continuously introduced into the wastewater samples from the bottom of the bubble column reactor at a rate of 0.83 mmol ozone per minute per liter of wastewater. The ozone exhaust gas generated during the wastewater treatment process was collected at the top of the bubble column reactor, treated to render it harmless, and then discharged. The treated wastewater was discharged from the bubble column reactor in batches. Samples were taken at 0, 15, 30, and 60 minutes after the ozone-containing oxygen was introduced and filtered through a 0.22 μm filter membrane. The TOC value of the water samples was tested, and the SMX mineralization rate was calculated. The results are as follows: Figure 6 As shown.

[0072] A control group consisting solely of ozone was also set up. The operation of the ozone control group was basically the same as that of the blank control group, except that no catalyst was added. The experimental results of the ozone control group were also as follows: Figure 6 As shown.

[0073] Depend on Figure 6 It can be seen that when the wastewater contains different concentrations of chloride ions, the SMX mineralization rate of the two experimental groups is consistent with that of the blank control group. The SMX mineralization rate is not affected by the coexisting chloride ions. At the same time, compared with the ozone control group alone, both experimental groups and the blank control group have higher SMX mineralization rates, indicating that the method of the present invention has strong anti-interference ability.

[0074] (3) Cyclic performance test of the catalyst

[0075] ① Dissolve SMX in water to form an SMX solution with a concentration of 20 mg / L, and use this SMX solution as simulated wastewater.

[0076] Simulated wastewater was added in batches from the top of the bubble column reactor. Catalyst was added to the simulated wastewater at a dosage of 0.4 g / L. Ozone-containing oxygen was then continuously introduced into the simulated wastewater from the bottom of the reactor at a rate of 0.83 mmol ozone per liter of wastewater per minute. Ozone tail gas generated during the wastewater treatment process was collected at the top of the reactor, treated to render it harmless, and then discharged. The treated wastewater was discharged from the bubble column reactor in batches. After reacting with ozone-containing oxygen for 60 minutes, samples were taken and filtered through a 0.22 μm filter membrane. The TOC of the simulated wastewater was tested, the SMX mineralization rate was calculated, and the catalyst was separated from the discharged treated wastewater by filtration.

[0077] ② The separated catalyst is added to fresh simulated wastewater, and the wastewater treatment operation in step ① is repeated.

[0078] ③ Repeat steps ① and ② until the catalyst has been recycled 5 times.

[0079] The change in SMX mineralization rate during recycling is as follows: Figure 7 As shown, by Figure 7 It can be seen that after the catalyst prepared in Example 1 was recycled 5 times, the SMX mineralization rate only decreased by 5%, which is still 30% higher than that of the SMX mineralization rate of the ozone system alone. The above experimental results show that the catalyst described in this invention has good stability and recyclability. Recycling the catalyst in the wastewater treatment process is beneficial to reducing the cost of wastewater treatment.

[0080] (4) Suitability test for pH value of wastewater

[0081] SMX was dissolved in water to form an SMX solution with a concentration of 20 mg / L. The pH of the SMX solution was adjusted to 3, 6, 7, 9 and 11 respectively using HNO3 and NaOH solutions to obtain a series of simulated wastewater with different pH values.

[0082] Simulated wastewater with different pH values ​​was added in batches from the top of the bubble column reactor. A catalyst was added to the simulated wastewater at a dosage of 0.4 g / L. Then, ozone-containing oxygen was continuously introduced into the simulated wastewater from the bottom of the bubble column reactor at a rate of 0.83 mmol ozone per liter of wastewater per minute. The ozone exhaust gas generated during the wastewater treatment process was collected at the top of the bubble column reactor, treated to render it harmless, and then discharged. The treated wastewater was discharged from the bubble column reactor in batches. After reacting with ozone-containing oxygen for 60 minutes, samples were taken, filtered through a 0.22 μm filter membrane, and the TOC of the simulated wastewater was tested. The SMX mineralization rate was calculated, and the results are as follows: Figure 8 As shown in the figure. A control group consisting solely of ozone was also set up. The operation of the ozone control group was basically the same as the previous steps, except that no catalyst was added. The experimental results of the ozone control group were also as shown in the figure. Figure 8 As shown.

[0083] Depend on Figure 8 It can be seen that when the pH value of the simulated wastewater is 3-11, after reacting for 60 minutes with ozone-containing oxygen and catalyst, the SMX mineralization rate reaches a level close to 60%. However, under the same wastewater pH value, when only ozone is introduced without catalyst, the SMX mineralization rate does not exceed 35%. This indicates that the method of the present invention has a wide applicable pH range for wastewater, and in practical applications, it can eliminate the need to adjust the wastewater pH value or reduce the consumption of acid and alkali for wastewater pH adjustment.

[0084] Example 3

[0085] In this embodiment, the preparation of the copper-cobalt bimetallic catalyst is basically the same as in Example 1, except that in step (2), the mass percentage of copper nitrate trihydrate and ZIF-67 is controlled to be 60%:40% (i.e., copper nitrate trihydrate and ZIF-67 account for 40% and 60% of the total mass of the two, respectively).

[0086] The following section examines the ability of the catalyst prepared in this embodiment to catalyze the degradation of pollutants by ozone oxidation, and investigates the active species generated during the degradation of pollutants through quenching experiments.

[0087] (1) Degradation effect on pollutants

[0088] OA was dissolved in water to form an OA solution with a concentration of 1 mmol / L, and this OA solution was used as simulated wastewater.

[0089] Simulated wastewater was added in batches from the top of the bubble column reactor. A catalyst was added to the simulated wastewater at a dosage of 0.4 g / L. Then, ozone-containing air was continuously introduced into the simulated wastewater from the bottom of the bubble column reactor at a rate of 5 mmol of ozone per minute per liter of wastewater for wastewater treatment. The ozone exhaust gas generated during the wastewater treatment process was collected at the top of the bubble column reactor, treated to render it harmless, and then discharged. The treated wastewater was discharged from the bubble column reactor in batches. After 30 minutes of reaction with ozone-containing air, samples were taken, filtered through a 0.22 μm filter membrane, and the OA concentration was tested. The OA removal rate was calculated, and the results showed that 100% degradation of OA could be achieved within 30 minutes of reaction.

[0090] (2) Quenching Experiment

[0091] tert-butanol, methanol, and DMSO were used as quenchers for free hydroxyl radicals, surface-adsorbed hydroxyl radicals, surface hydroxyl radicals, and surface atomic oxygen, respectively.

[0092] OA was dissolved in water to form an OA solution with a concentration of 1 mmol / L, which was used as simulated wastewater. Three experimental groups and one blank control group (without quencher) were set up. In the three experimental groups, tert-butanol, methanol, and DMSO were added to a concentration of 200 mmol / L, respectively. Details are as follows:

[0093] Simulated wastewater was added in batches from the top of the bubble column reactor. Appropriate quenching agents (no quenching agent was added to the blank control group) and catalysts were added to each simulated wastewater. Then, ozone-containing air was continuously introduced into the simulated wastewater from the bottom of the bubble column reactor at a rate of 5 mmol of ozone per minute per liter of wastewater for wastewater treatment. Ozone tail gas generated during the wastewater treatment process was collected at the top of the bubble column reactor, treated to render it harmless, and then discharged in batches. The treated wastewater was discharged from the bubble column reactor in batches. The catalyst dosage was controlled at 0.4 g / L. After 30 minutes of reaction with ozone-containing air, samples were taken, filtered through a 0.22 μm filter membrane, and the OA concentration was tested to calculate the OA removal rate.

[0094] Test results show that tert-butanol has no inhibitory effect on OA degradation, methanol significantly inhibits OA degradation, and DMSO has the most significant inhibitory effect on OA degradation. This indicates that the catalyst of the present invention does not produce free hydroxyl radicals among the main active species when catalyzing ozone oxidation to degrade OA. Instead, it mainly consists of surface atomic oxygen and surface hydroxyl radicals. In other words, the catalyst prepared based on this embodiment can successfully construct a surface catalytic ozone oxidation process.

[0095] Example 4

[0096] In this embodiment, the catalyst prepared in Example 3 is used to catalyze the ozone oxidation degradation of simulated wastewater containing SMX. The steps are as follows:

[0097] SMX was dissolved in water to form an SMX solution with a concentration of 20 mg / L and a pH value between 6 and 7. This SMX solution was used as simulated wastewater.

[0098] Simulated wastewater was added in batches from the top of the bubble column reactor. A catalyst was added to the simulated wastewater at a dosage of 0.4 g / L. Then, ozone-containing air was continuously introduced into the simulated wastewater from the bottom of the bubble column reactor at a rate of 2.5 mmol of ozone per minute per liter of wastewater. Ozone exhaust gas generated during the wastewater treatment process was collected at the top of the bubble column reactor, treated to render it harmless, and then discharged. The treated wastewater was discharged from the bubble column reactor in batches. Samples were taken at 0, 15, 30, and 60 min of reaction with ozone-containing air, filtered through a 0.22 μm filter membrane, and the TOC concentration of the simulated wastewater was tested to calculate the SMX mineralization rate. The results showed that the SMX mineralization rate reached 70% at 60 min of reaction.

[0099] A control group with a separate ozone reaction system was also set up. The operation of the control group was basically the same as the above-described steps, except that no catalyst was added. The results showed that the SMX mineralization rate of the ozone oxidation system alone was only about 35% after 60 minutes of reaction.

[0100] Example 5

[0101] In this embodiment, the preparation of the copper-cobalt bimetallic catalyst is basically the same as in Example 1, except that: in step (1), the mass percentage of cobalt nitrate hexahydrate and dimethylimidazole is controlled at 37%:63%, and in step (2), the mass percentage of copper nitrate trihydrate and ZIF-67 is controlled at 40%:60%.

[0102] The following section examines the ability of the catalyst prepared in this embodiment to catalyze the degradation of pollutants by ozone oxidation, and investigates the active species generated during the degradation of pollutants through quenching experiments.

[0103] (1) Degradation effect on pollutants

[0104] OA was dissolved in water to form an OA solution with a concentration of 0.5 mmol / L, and this OA solution was used as simulated wastewater.

[0105] Simulated wastewater was added in batches from the top of the bubble column reactor. A catalyst was added to the simulated wastewater at a dosage of 2 g / L. Then, ozone-containing air was continuously introduced into the simulated wastewater from the bottom of the bubble column reactor at a rate of 1.2 mmol of ozone per liter of wastewater per minute. The ozone exhaust gas generated during the wastewater treatment process was collected at the top of the bubble column reactor, treated to render it harmless, and then discharged. The treated wastewater was discharged from the bubble column reactor in batches. After 20 minutes of reaction with ozone-containing air, samples were taken, filtered through a 0.22 μm filter membrane, and the OA concentration was tested. The OA removal rate was calculated, and the results showed that 100% degradation of OA could be achieved after 20 minutes of reaction.

[0106] (2) Quenching Experiment

[0107] tert-butanol, methanol, and DMSO were used as quenchers for free hydroxyl radicals, surface-adsorbed hydroxyl radicals, surface hydroxyl radicals, and surface atomic oxygen, respectively.

[0108] OA was dissolved in water to form an OA solution with a concentration of 0.5 mmol / L, which was used as simulated wastewater. Three experimental groups and one blank control group (without quencher) were set up. In the three experimental groups, tert-butanol, methanol, and DMSO were added to a concentration of 200 mmol / L, respectively. Details are as follows:

[0109] Simulated wastewater was added in batches from the top of the bubble column reactor. Appropriate quenching agents (no quenching agent was added to the blank control group) and catalysts were added to each wastewater. Then, ozone-containing air was continuously introduced into the simulated wastewater from the bottom of the bubble column reactor at a rate of 1.2 mmol of ozone per liter of wastewater per minute. Ozone tail gas generated during the wastewater treatment process was collected at the top of the bubble column reactor, treated to render it harmless, and then discharged. The treated wastewater was discharged from the bubble column reactor in batches. The catalyst dosage was controlled at 2 g / L. After 30 minutes of reaction with ozone-containing air, samples were taken, filtered through a 0.22 μm filter membrane, and the OA concentration was tested to calculate the OA removal rate.

[0110] Test results show that tert-butanol has no inhibitory effect on OA degradation, methanol significantly inhibits OA degradation, and DMSO has the most significant inhibitory effect on OA degradation. This indicates that the catalyst does not produce free hydroxyl radicals among the main active species generated during the catalytic ozone oxidation degradation of OA, but mainly consists of surface atomic oxygen and surface hydroxyl radicals. Therefore, the catalyst prepared based on this embodiment can successfully construct a surface catalytic ozone oxidation process.

[0111] Example 6

[0112] In this embodiment, the catalyst prepared in Example 3 is used to catalyze the ozone oxidation degradation of simulated wastewater containing p-nitrophenol (PNP). The steps are as follows:

[0113] PNP was dissolved in water to form a PNP solution with a concentration of 50 mg / L, and this PNP solution was used as simulated wastewater.

[0114] Simulated wastewater was added in batches from the top of the bubble column reactor. Catalyst was added to the simulated wastewater at a dosage of 2 g / L. Ozone-containing air was then continuously introduced into the simulated wastewater from the bottom of the reactor at a rate of 0.56 mmol ozone per minute per liter of wastewater. Ozone tail gas generated during the wastewater treatment process was collected at the top of the reactor, treated to render it harmless, and then discharged. The treated wastewater was discharged from the bubble column reactor in batches. The catalyst dosage was controlled such that after 60 minutes of reaction with ozone-containing air, a sample was taken, filtered through a 0.22 μm filter membrane, and the TOC concentration of the simulated wastewater was tested to calculate the PNP mineralization rate. The results showed that in this embodiment, the PNP mineralization rate reached 95% after 60 minutes of reaction.

[0115] Example 7

[0116] In this embodiment, the copper-cobalt bimetallic catalyst is prepared by the following steps:

[0117] (1) Cobalt chloride hexahydrate and 2-methylimidazole were added to anhydrous methanol and the mass percentage of cobalt chloride hexahydrate to 2-methylimidazole was controlled to be 37%:63% (that is, cobalt chloride hexahydrate and 2-methylimidazole accounted for 37% and 63% of the total mass of the two, respectively). The mixture was stirred thoroughly and then stirred vigorously at room temperature for 4 hours. After that, it was allowed to stand at room temperature for 24 hours to obtain ZIF-67.

[0118] (2) Add copper nitrate trihydrate and ZIF-67 to anhydrous ethanol, and control the mass percentage of copper nitrate trihydrate to ZIF-67 to be 40%:60% (that is, copper nitrate trihydrate and ZIF-67 account for 40% and 60% of the total mass of the two, respectively). Then transfer it to a stainless steel autoclave with Teflon lining, react at 240℃ for 12h, filter, wash the obtained solid phase with ethanol, dry, grind, and obtain the reaction precursor.

[0119] (3) The reaction precursor was placed in a muffle furnace and calcined at 550°C for 2 hours in an air atmosphere. The calcined product was washed with water to remove unreacted substances and then ground to obtain a copper-cobalt bimetallic catalyst with a particle size in the nanometer range.

[0120] The following section examines the ability of the catalyst prepared in this embodiment to catalyze the degradation of pollutants by ozone oxidation, and investigates the active species generated during the degradation of pollutants through quenching experiments.

[0121] (1) Degradation effect on pollutants

[0122] OA was dissolved in water to form an OA solution with a concentration of 0.5 mmol / L, and this OA solution was used as simulated wastewater.

[0123] Simulated wastewater was added in batches from the top of the bubble column reactor. A catalyst was added to the simulated wastewater at a dosage of 0.4 g / L. Then, ozone-containing air was continuously introduced into the wastewater from the bottom of the bubble column reactor at a rate of 3 mmol of ozone per minute per liter of wastewater for wastewater treatment. The ozone tail gas generated during the wastewater treatment process was collected at the top of the bubble column reactor, treated to render it harmless, and then discharged. The treated wastewater was discharged from the bubble column reactor in batches. After 30 minutes of reaction with ozone-containing air, samples were taken, filtered through a 0.22 μm filter membrane, and the OA concentration was tested. The OA removal rate was calculated, and the results showed that 100% degradation of OA could be achieved after 30 minutes of reaction.

[0124] (2) Quenching Experiment

[0125] tert-butanol, methanol, and DMSO were used as quenchers for free hydroxyl radicals, surface-adsorbed hydroxyl radicals, surface hydroxyl radicals, and surface atomic oxygen, respectively.

[0126] OA was dissolved in water to form an OA solution with a concentration of 0.5 mmol / L, which was used as simulated wastewater. Three experimental groups and one blank control group (without quencher) were set up. In the three experimental groups, tert-butanol, methanol, and DMSO were added to a concentration of 200 mmol / L, respectively. Details are as follows:

[0127] Simulated wastewater was added in batches from the top of the bubble column reactor. Appropriate quenching agents (no quenching agent was added to the blank control group) and catalysts were added to each simulated wastewater. Then, ozone-containing air was continuously introduced into the simulated wastewater from the bottom of the bubble column reactor at a rate of 3 mmol of ozone per minute per liter of wastewater for wastewater treatment. Ozone tail gas generated during the wastewater treatment process was collected at the top of the bubble column reactor, treated to render it harmless, and then discharged in batches. The treated wastewater was discharged from the bubble column reactor in batches. The catalyst dosage was controlled at 0.4 g / L. After 30 minutes of reaction with ozone-containing air, samples were taken, filtered through a 0.22 μm filter membrane, and the OA concentration was tested to calculate the OA removal rate.

[0128] Test results show that tert-butanol has no inhibitory effect on the degradation of OA, the addition of methanol significantly inhibits the degradation of OA, and the addition of DMSO has the most obvious inhibitory effect on the degradation of OA. This indicates that when the catalyst catalyzes the ozone oxidation degradation of OA, the main active species produced do not contain free hydroxyl radicals, but are mainly surface atomic oxygen and surface hydroxyl radicals.

[0129] Example 8

[0130] In this embodiment, the copper-cobalt bimetallic catalyst is prepared by the following steps:

[0131] (1) Cobalt nitrate hexahydrate and 2-methylimidazole were added to anhydrous methanol, and the mass percentage of cobalt nitrate hexahydrate to 2-methylimidazole was controlled to be 45%:55% (i.e., cobalt nitrate hexahydrate and 2-methylimidazole accounted for 45% and 55% of the total mass of the two, respectively). The mixture was stirred thoroughly and then stirred vigorously at room temperature for 30 min. After that, it was allowed to stand at room temperature for 48 h to obtain ZIF-67.

[0132] (2) Add copper acetate monohydrate and ZIF-67 to anhydrous ethanol, and control the mass percentage of copper acetate monohydrate to ZIF-67 to be 45%:55% (that is, copper acetate monohydrate and ZIF-67 account for 45% and 55% of the total mass of the two, respectively). Then transfer it to a stainless steel autoclave with Teflon lining, react at 220℃ for 12h, filter, wash the obtained solid phase with ethanol, dry, grind, and obtain the reaction precursor.

[0133] (3) The reaction precursor was placed in a muffle furnace and calcined at 350°C for 5 hours in an air atmosphere. The calcined product was washed with water to remove unreacted substances and then ground to obtain a copper-cobalt bimetallic catalyst with a particle size in the nanometer range.

[0134] The following section examines the ability of the catalyst prepared in this embodiment to catalyze the degradation of pollutants by ozone oxidation, and investigates the active species generated during the degradation of pollutants through quenching experiments.

[0135] (1) Degradation effect on pollutants

[0136] OA was dissolved in water to form an OA solution with a concentration of 0.1 mmol / L, and this OA solution was used as simulated wastewater.

[0137] Simulated wastewater was added in batches from the top of the bubble column reactor. A catalyst was added to the simulated wastewater at a dosage of 0.4 g / L. Ozone-containing air was then continuously introduced into the simulated wastewater from the bottom of the reactor at a rate of 0.42 mmol ozone per liter of wastewater per minute. Ozone tail gas generated during the wastewater treatment process was collected at the top of the reactor, treated to render it harmless, and then discharged. The treated wastewater was discharged from the bubble column reactor in batches. After 30 minutes of reaction with ozone-containing air, samples were taken, filtered through a 0.22 μm filter membrane, and the OA concentration was tested. The OA removal rate was calculated, and the results showed that 100% degradation of OA could be achieved within 30 minutes of reaction.

[0138] (2) Quenching Experiment

[0139] tert-butanol, methanol, and DMSO were used as quenchers for free hydroxyl radicals, surface-adsorbed hydroxyl radicals, surface hydroxyl radicals, and surface atomic oxygen, respectively.

[0140] OA was dissolved in water to form an OA solution with a concentration of 0.1 mmol / L, which was used as simulated wastewater. Three experimental groups and one blank control group (without quencher) were set up. In the three experimental groups, tert-butanol, methanol, and DMSO were added to a concentration of 200 mmol / L, respectively. Details are as follows:

[0141] Simulated wastewater was added in batches from the top of the bubble column reactor. Appropriate quenching agents (no quenching agent was added to the blank control group) and catalysts were added to each simulated wastewater. Then, ozone-containing air was continuously introduced into the simulated wastewater from the bottom of the bubble column reactor at a rate of 0.42 mmol ozone per liter of wastewater per minute. Ozone tail gas generated during the wastewater treatment process was collected at the top of the bubble column reactor, treated to render it harmless, and then discharged in batches. The treated wastewater was discharged from the bubble column reactor in batches. The catalyst dosage was controlled at 0.4 g / L. After 30 minutes of reaction with ozone-containing air, samples were taken, filtered through a 0.22 μm filter membrane, and the OA concentration was tested to calculate the OA removal rate.

[0142] Test results show that tert-butanol has no inhibitory effect on the degradation of OA, the addition of methanol significantly inhibits the degradation of OA, and the addition of DMSO has the most obvious inhibitory effect on the degradation of OA. This indicates that when the catalyst catalyzes the ozone oxidation degradation of OA, the main active species produced do not contain free hydroxyl radicals, but are mainly surface atomic oxygen and surface hydroxyl radicals.

[0143] Example 9

[0144] This embodiment uses the catalyst prepared in Example 8 to catalyze the ozone oxidation degradation of wastewater containing diclofenac. The steps are as follows:

[0145] Diclofenac was dissolved in water to form a diclofenac solution with a concentration of 20 mg / L, and this diclofenac solution was used as simulated wastewater.

[0146] Simulated wastewater was added in batches from the top of the bubble column reactor. A catalyst was added to the simulated wastewater at a dosage of 0.5 g / L. Then, ozone-containing air was continuously introduced into the wastewater from the bottom of the bubble column reactor at a rate of 1.25 mmol ozone per liter of wastewater per minute. The ozone exhaust gas generated during the wastewater treatment process was collected at the top of the bubble column reactor, treated to render it harmless, and then discharged. The treated wastewater was discharged from the bubble column reactor in batches. After 60 minutes of reaction with ozone-containing air, a sample was taken, filtered through a 0.22 μm filter membrane, and the TOC concentration of the simulated wastewater was tested to calculate the diclofenac mineralization rate. The results showed that in this embodiment, the diclofenac mineralization rate reached 80% after 60 minutes of reaction.

[0147] Example 10

[0148] In this embodiment, the catalyst prepared in Example 1 is used to catalytically oxidize and treat the secondary effluent of chemical wastewater. The chemical wastewater (i.e., industrial tailwater) has a chemical oxygen demand (COD) concentration of 170 mg / L, a pH value of 8.10, and concentrations of chloride ions, nitrate ions, and sulfate ions of 1531 mg / L, 35 mg / L, and 1213 mg / L, respectively. The operation is as follows:

[0149] Industrial wastewater was added in batches from the top of the bubble column reactor. A catalyst was added to the wastewater at a dosage of 0.4 g / L. Ozone-containing air was then continuously introduced into the wastewater from the bottom of the reactor at a rate of 1.25 mmol ozone per minute per liter of wastewater. The ozone exhaust gas generated during the wastewater treatment process was collected at the top of the reactor, treated to render it harmless, and then discharged. The treated wastewater was discharged from the bubble column reactor in batches. Samples were taken after 30, 60, 90, and 120 minutes of reaction with ozone-containing air, filtered through a 0.22 μm filter membrane, and the COD concentration of the water samples was tested. The COD removal rate was calculated, and the results are as follows: Figure 9 As shown.

[0150] Simultaneously, a control group with a separate ozone reaction system was set up. The operation of the control group was basically the same as the operation described above, except that no catalyst was added. The results were also as expected. Figure 9 As shown.

[0151] Depend on Figure 9 It can be seen that the method of the present invention has a COD removal rate of 70% for industrial wastewater after 120 min of reaction, while the control group has a COD removal rate of only 15% for industrial wastewater after 120 min of reaction.

[0152] Example 11

[0153] In this embodiment, the catalyst prepared in Example 1 is used to catalytically oxidize and treat the secondary effluent of pharmaceutical wastewater. The COD concentration of the secondary effluent is 256 mg / L, the pH value is 8.86, and the concentrations of chloride ions, nitrate ions, and sulfate ions are 4528 mg / L, 5 mg / L, and 2190 mg / L, respectively. The operation is as follows:

[0154] Pharmaceutical wastewater secondary effluent was added in batches from the top of the bubble column reactor. A catalyst was added to the secondary effluent at a dosage of 0.5 g / L. Ozone-containing air was then continuously introduced into the secondary effluent from the bottom of the bubble column reactor at a rate of 1.9 mmol ozone per minute per liter of wastewater. Ozone exhaust gas generated during the wastewater treatment process was collected at the top of the bubble column reactor, treated to render it harmless, and then discharged. The treated wastewater was discharged from the bubble column reactor in batches. Samples were taken after reacting with ozone-containing air for 30, 60, 90, and 120 minutes, filtered through a 0.22 μm filter membrane, and the COD concentration was tested. The COD removal rate was calculated, and the results are as follows: Figure 10 As shown.

[0155] Simultaneously, a control group with a separate ozone reaction system was set up. The operation of the control group was basically the same as the operation described above, except that no catalyst was added. The results were also as expected. Figure 10 As shown.

[0156] Depend on Figure 10 It can be seen that the method of the present invention has a COD removal rate of 90% for the secondary effluent of pharmaceutical wastewater after 120 min of reaction, while the control group has a COD removal rate of only 55% for the secondary effluent of pharmaceutical wastewater after 120 min of reaction.

Claims

1. A method for deep wastewater treatment based on surface catalytic ozone oxidation, characterized in that, Includes the following steps: Wastewater is continuously or batch-added into a closed-loop wastewater treatment device from the top. A catalyst is added to the wastewater, and ozone-containing gas is continuously introduced into the wastewater from the bottom for treatment. The ozone tail gas generated during the wastewater treatment process is collected at the top of the device and discharged after harmless treatment. The treated wastewater is discharged continuously or in batches. During the wastewater treatment process, the catalyst catalyzes ozone to generate surface hydroxyl radicals and surface atomic oxygen adsorbed on the catalyst surface, which degrade organic pollutants in the wastewater. The catalyst is a nano-scale copper-cobalt bimetallic catalyst composed of CuO and Co3O4, with CuO and Co3O4 forming a heterostructure. The catalyst is prepared as follows: copper source and ZIF-67 are added to solvent at a mass percentage of (40%~60%):(40%~60%), transferred to a Teflon-lined stainless steel autoclave, and reacted at 120~240 ℃ for 4~12 h. After solid-liquid separation, the obtained solid phase is washed with solvent and then pulverized to obtain the reaction precursor. The reaction precursor is calcined at 350~550 ℃ for 1~5 h, washed to remove unreacted substances from the calcined product, dried, and pulverized to obtain the catalyst.

2. The wastewater deep treatment method based on surface catalytic ozone oxidation according to claim 1, characterized in that, The ZIF-67 is prepared by mixing cobalt source and dimethylimidazole in a solvent at a mass percentage of (37%~47%):(53%~63%), reacting at 20~50 °C for 0.5~4 h, and then allowing it to stand at room temperature for 24~48 h to precipitate.

3. The wastewater deep treatment method based on surface catalytic ozone oxidation according to claim 1, characterized in that, In the preparation of the catalyst, the reaction precursor is calcined in an atmosphere of air, oxygen, or a mixture of air and oxygen.

4. The wastewater deep treatment method based on surface catalytic ozone oxidation according to any one of claims 1 to 3, characterized in that, The dosage of catalyst in wastewater should be controlled at 0.2~10 g / L.

5. The wastewater deep treatment method based on surface catalytic ozone oxidation according to any one of claims 1 to 3, characterized in that, Ozone-containing gas is introduced into the wastewater at a rate of 0.4 to 5 mmol of ozone per minute per liter of wastewater.

6. The wastewater deep treatment method based on surface catalytic ozone oxidation according to any one of claims 1 to 3, characterized in that, The ozone-containing gas is either ozone-containing air or ozone-containing oxygen.

7. The wastewater deep treatment method based on surface catalytic ozone oxidation according to any one of claims 1 to 3, characterized in that, Control the pH of the wastewater to 3-11.

8. The wastewater deep treatment method based on surface catalytic ozone oxidation according to any one of claims 1 to 3, characterized in that, When a continuous wastewater inflow and continuous wastewater outflow method is adopted, the hydraulic retention time of the wastewater in the closed wastewater treatment process should be controlled to be 30~120 min; when a batch wastewater inflow and batch wastewater outflow method is adopted, the wastewater treatment time should be controlled to be 20~180 min.

Citation Information

Patent Citations

  • Ozonization water processing method taking copper / cobalt nano composite material as catalyst

    CN103708601A